Bacterial vaginosis – diagnostic dilemma and implications - Atanasievska, Sonja; Nenadić, Dane; Stanković, Slaviša; Protić-Đokić, Vesna; Ristanović, Elizabeta (Vojnosanitetski pregled, 2023)
Background/Aim. Bacterial vaginosis (BV) is one of the most common microbial dysbiosis, characterized by a decrease of Lactobacillus spp. with an increase of other anaerobic bacteria species [Gardnerella (G.) vaginalis, Atopobium (A.) vaginae, Prevotella spp, Mobiluncus spp, etc.] causing serious gynecological and obstetric complications. Therefore, it is particularly important to have accurate and reliable diagnostic standards. The aim of this study was to compare the results of various diagnostic methods for detecting BV, such as Amsel, Nugent, and Ison and Hay criteria, as well as multiplex quantitative real-time polymerase chain reaction (mqRT-PCR) test. Methods. This study involved vaginal swabs from 235 patients of reproductive age. Nugent criteria were used as the ‘gold standard’ compared with Amsel and Ison/Hay criteria as well as mqRT-PCR test based on the detection and quantification of G. vaginalis, A. vaginae, Lactobacillus spp., and total concentration of bacterial DNA. The kappa coefficient was employed to measure agreement between tests. Results. Our analysis demonstrated excellent agreement between Ison/Hay criteria and Nugent scores (kappa = 0.95), good agreement between Amsel and Nugent criteria (kappa = 0.78), while between Nugent criteria and mqRT-PCR test agreement was moderate (kappa = 0.59). Total agreements of Ison/Hay, Amsel, and mqRT-PCR against Nugent scores were 94.9%, 90.2%, and 74%, respectively. Nugent methods classified the highest number of intermediate patients - 60 (25.2%). The largest number of BV patients was detected by the mqRT-PCR method, while the largest number of healthy patients was detected by Amsel criteria. Conclusion. The mqRT-PCR is the best choice for BV diagnosis because it is more efficient at differentiating patients with intermediate results. Compared to Amsel and Nugent methods that group patients into 2 or 3 categories, the mqRT-PCR method recognizes other conditions of vaginal flora important for correct diagnoses and application of better therapeutic approaches, as well as preventing possible clinical consequences of this dysbiosis.